2015
DOI: 10.5301/ijao.5000380
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Polynephron Dialysis Membrane considering New Aspects of Biocompatibility

Abstract: The use of polynephron for 4 months reduces the percentage of CD14+CD16+ compared to helixone and polyamide, suggesting a better profile regarding activation of the inflammatory response. These findings could be explained by a better biocompatibility or an increased reduction of medium-sized toxic molecules.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…The percentages of proinflammatory monocytes in HD patients are higher than in patients with advanced CKD before the start of the technique (13) and are also higher than in PD patients (17). These findings have been attributed to the effects of the HD technique and, in this regard, a decrease of proinflammatory monocytes has been outlined including biocompatible membranes (18), with the HDF technique (19)(20)(21) and with use of drugs such as losartan, an angiotensin II receptor antagonist (22). However, given our results, this finding can also be explained by the presence of RRF, which is more common in CKD and not so in dialysis, and also usually in PD patients, even though Heine et al (17) do not include this parameter in their work.…”
Section: Discussionmentioning
confidence: 95%
“…The percentages of proinflammatory monocytes in HD patients are higher than in patients with advanced CKD before the start of the technique (13) and are also higher than in PD patients (17). These findings have been attributed to the effects of the HD technique and, in this regard, a decrease of proinflammatory monocytes has been outlined including biocompatible membranes (18), with the HDF technique (19)(20)(21) and with use of drugs such as losartan, an angiotensin II receptor antagonist (22). However, given our results, this finding can also be explained by the presence of RRF, which is more common in CKD and not so in dialysis, and also usually in PD patients, even though Heine et al (17) do not include this parameter in their work.…”
Section: Discussionmentioning
confidence: 95%
“…Since it has been clear that the effects of uremia on DCs are detrimental (2036), several therapeutic interventions have been proposed to prevent or at least limit uremiarelated cellular and/or biological alterations of immunologic cells, such as the use of biocompatible HD membranes and the introduction of hemofiltration (44454647). In addition, it has been suggested that improving HD clearance using a highly efficient dialyzer has the potential to improve the immunologic dysfunction in patients with ESRD.…”
Section: Modulation Of DC Function In Patients With Esrdmentioning
confidence: 99%
“…Biomaterial implants and medical devices are widely used today and their performance is crucial for the safety of patients and their quality of life (1). Nevertheless, the implantation of any foreign material or device will trigger a cascade of inflammatory responses, which can lead to chronic inflammation and fibrotic encapsulation, resulting in the failure of implants and devices (2).…”
Section: Introductionmentioning
confidence: 99%